MANAJEMEN PROGRAM PENDIDIKAN KESETARAAN PADA PESANTREN SALAFIYAH DI PONDOK PESANTREN DARUL AMIN PALANGKA RAYA - Dila Nour Padila; Ahmadi Ahmadi; Slamet Riyadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the management of the Equality Education Program in Salafiyah Islamic Boarding Schools (PKPPS) at Pondok Pesantren Darul Amin Palangka Raya, focusing on the Wustho level. The study is motivated by the gap between students’ need for formal educational recognition and the dominance of religious learning in salafiyah pesantren. Although previous studies have examined PKPPS, most have focused on program evaluation based on policy compliance, with limited attention to the operational management aspects, particularly planning and implementation at the institutional level. This limitation indicates a significant research gap, especially in the context of pesantren outside Java. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. Data were analyzed using the interactive model of Miles and Huberman. The findings reveal that program management has been implemented through systematic planning involving internal coordination and external collaboration with the Ministry of Religious Affairs. The implementation combines diniyah (religious) activities and general academic learning based on the 2013 Curriculum. However, an imbalance in time allocation between religious and academic learning was identified, indicating that curriculum integration has not yet been optimal. The novelty of this study lies in its in-depth analysis of PKPPS management at the micro level of pesantren, particularly within the local context of Central Kalimantan.